Muhasabah Sebagai Metode Dalam Memotivasi Penghafal Al-Qur’an : (Studi Deskriptif Kualitatif di Pondok Tahfidz Saba Gianyar Bali) - Aini Nabila (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD Cianjur, 2022)
Memorizing the Qur’an is an activity that requires high motivation. Motivation can go up and down according to the situation and conditions. One strategy that can be used to generate motivation is the Muhasabah method. This study aims to examine the extent to which the Muhasabah method can arouse the motivation of the memorizers of the Qur’an. The method chosen to carry out this research is descriptive qualitative using observation and interview techniques as a technique in collecting data. This research conducted at the Saba Qur’an memorization boarding school in Gianyar Bali. The researcher found that in the process of memorizing the Qur’an, the memorizers experienced various obstacles which resulted in a decrease in motivation to memorize. Therefore, the Muhasabah method is used as an effort to increase motivation. The conclusion of this study is the Muhasabah method can be an option to increase the motivation of memorizing the Qur’an because with Muhasabah, self-awarness will emerge to become even better.